Blending Naqli And Aqli Elements In Internship Programs : Insights From Students’ Essays And Reportsrts - Nusairah Ramli; Hajar Hazwani Abdullah (USIM Press, 2024)
Journal of Islamic Social Sciences and Humanities (Al-'Abqari) Volume 29 No.1 Page (135-150)